Long-wavelength Discrepancies Between the Australian Gravity Field and EIGEN-2 CHAMP Data - Featherstone, Will (Springer, 2005)
Long-wavelength differences (in the ~1,100 km to ~6,500 km waveband) are evident between Australian free-air gravity anomalies and those implied by EIGEN-2 to degree 32, which is derived purely from CHAMP data. They reach ~11 mGal for the Australian land gravity anomalies and over ~15 mGal for the [unadjusted] ship-track grav-ity anomalies. These long-wavelength differences are used to quantify the effect on the gravimetric geoid model. Using an unmodified Stokes kernel and no limit on the cap radius (i.e., all terrestrial gravity in the region), the resulting effect on the geoid is between -0.72m and 0.13m, though the large negative value is attributed to a lack of gravity data to the north of Australia. Using a modified Stokes kernel and a one-degree cap radius as a high-pass filter, the resulting effect on the geoid is between -0.28m and 0.10m. Applying the latter and EIGEN-2 to degree 32 as corrections to AUS-Geoid98 yields a small, but insignificant, improvement in the fit to nation-wide GPS-levelling data.